DEMOGRAPHIC POTENTIAL AS A COMPONENT ELEMENT OF ECONOMIC SECURITY IN THE REGION - V. V. Karpov; K. V. Petrenko (Вестник СибАДИ, 2018)
Introduction. The article examines approaches to determining one of the most important characteristics of regional economic security - demographic potential. The correct interpretation of this concept makes it possible to monitor and develop political postulates of actions aimed at improving the socio-economic bases of demographic processes. The list of planned activities, built in accordance with the specified content of the concept of “demographic potential”, is adequate to the existing qualitative and quantitative characteristics of the population and would avoid crisis situations in the economy and social sphere of the region.Materials and methods. The study of approaches to determining the demographic potential and its role in the formation of the labor potential of the territories, show the absence of unified methodological bases for estimating and predicting the processes of forming the demographic potential for different hierarchical levels of government. Moreover, the need to consider the concept of demographic potential is dictated by the increased attention to potential demography, on the one hand, as a scientific direction, conditioned by the study of internal dynamics and inertia of the population reproduction processes, and on the other hand, as a problem having practical significance in ensuring the functioning of regional employment opportunities for people.Results. As a result, the research demonstrates the presence of a large number of approaches and formulations of the “demographic potential” concept, which are conditioned by different theoretical and methodological approaches to disclosure of the demographic processes content depending on the research objectives. According to the authors, at the current level of regional qualification of Russia, adjustments are needed in the mode of the labor potential reproduction due to the sharp increase in the outflow of population, especially in the Siberian regions. Demographic potential as an economic category requires in such conditions the increased attention of scientists and also political structures. It is the basis for the identification of hidden opportunities to provide population and population structure for different demographic characteristics.Discussion and conclusions. The analysis and solution of the problems of the labor potential reproduction is now at the forefront of ensuring economic security of the regions. To ensure such problems is not possible without the presence and proper understanding of the content and conditions for the formation of the demographic potential in conditions of intensive migration between the Siberian and European territories of the country.